Dignity and Dreams - Sykes, Jennifer; Križ, Katrin; Edin, Kathryn; Halpern-Meekin, Sarah (American Sociological Review, 2015)
Money has meaning that shapes its uses and social significance, including the monies low-income families draw on for survival: wages, welfare, and the Earned Income Tax Credit (EITC). This study, based on in-depth interviews with 115 low-wage EITC recipients, reveals the EITC is an unusual type of government transfer. Recipients of the EITC say they value the debt relief this government benefit brings. However, they also perceive it as a just reward for work, which legitimizes a temporary increase in consumption. Furthermore, unlike other means-tested government transfers, the credit is seen as a springboard for upward mobility. Thus, by conferring dignity and spurring dreams, the EITC enhances feelings of citizenship and social inclusion.